Plain Language Movements: Democratization of information and active citizenship (Research, Society and Development, 2025)
This article aims to advocate for the importance of integrating Plain Language (SL) into public policy frameworks as a way to ensure more transparent dialogue between public officials and the public, strengthening democratic principles and expanding citizen participation, with as few asymmetries as possible. To this end, documentary research was conducted using direct and indirect sources, including a search for authors in the literature. This qualitative, reflective study, specifically a narrative literature review, was based on deductive and analytical-interpretative reasoning. The results and discussion included a conceptual breakdown of SL, from the perspective of an essential tool for democratizing public communication, promoting social inclusion, and strengthening government transparency. Similarly, SL aims to simplify official texts, making them accessible to all citizens, regardless of education level or social context. The study also explores the global origins of these movements, their adaptation to the Brazilian context, and the cultural and institutional challenges of their implementation. Finally, national and international initiatives are highlighted that demonstrate the positive impact of LS in reducing bureaucratic barriers, strengthening active citizenship and building a more equitable society.